Evaluation of temperature rise with different curing methods and units in two composite resins - Tabatabaei M; Mirzaei M; Ataei M; Motevaselian F (Tehran University of Medical Sciences, 2006)
Background and Aim: The majority of commercial curing units in dentistry are of halogen lamp type. The new polymerizing units such as blue LED are introduced in recent years. One of the important side effects of light curing is the temperature rise in composite resin polymerization which can affect the vitality of tooth pulp. The purpose of this study was to evaluate the temperature rise in two different composite resins during polymerization with halogen lamps and blue LED. Materials and Methods: This experimental study investigated the temperature rise in two different composites (Hybrid, Tetric Ceram/Nanofilled, Filteke Supreme) of A2 shade polymerized with two halogen lamps (Coltolux 50, 350 mW/cm2 and Optilux 501 in standard, 820 mW/cm2 and Ramp, 100-1030 mW/cm2 operating modes) and one blue LED with the intensity of 620 mW/cm2. Five samples for each group were prepared and temperature rise was monitored using a k-type thermocouple. Data were analyzed by one-way ANOVA, two-way ANOVA and Tukey HSD tests with P<0.05 as the limit of significance. Results: Light curing units and composite resins had statistically significant influence on the temperature rise (p<0.05). Significantly, lower temperature rise occurred in case of illumination with Coltolux 50.There was no significant difference between Optilux 501 in standard curing mode and LED. Tetric Ceram showed higher temperature rise. Conclusion: According to the results of this study the high power halogen lamp and LED could produce significant heat which may be harmful to the dental pulp.